The Uptake of Ethinyl-Estradiol and Cortisol From Water by Mussels (Mytilus spp.) - Katsiadaki, Ioanna; Schwarz, Tamar I.; Cousins, Alex R. O.; Scott, Alexander P. (Frontiers in Endocrinology, 2021)
Previous toxicokinetic studies have shown that mussels can a) readily absorb the three main mammalian sex steroids, oestradiol (E2), testosterone (T) and progesterone (P) from water and b) have a strong ability to store E2 and the 5α-reduced metabolites of T and P in the form of fatty acid esters. These esters were shown to have half-lives that were measured in weeks (i.e., they are not subject to fast depuration). The present study looked at the toxicokinetic profile of two other common steroids that are found in water. The potent synthetic oestrogen, ethinyl oestradiol (EE2; one of the two components of ‘the pill’), and cortisol, a natural stress steroid in vertebrates. In the first few hours of uptake, tritiated EE2 was found to be taken up at a similar rate to tritiated E2. However, the levels in the water plateaued sooner than E2. The ability of the animals to both esterify and sulphate EE2 was found to be much lower than E2, but nevertheless did still take place. After 24 h of exposure, the majority of radiolabelled EE2 in the animals was present in the form of free steroid, contrary to E2, which was esterified. This metabolism was reflected in a much lower half-life (of only 15 h for EE2 in the mussels as opposed to 8 days for E2 and >10 days for T and P). Intriguingly, hardly any cortisol (in fact none at all in one of the experiments) was absorbed by the mussels. The implications of this finding in both toxicokinetic profiling and evolutionary significance (why cortisol might have evolved as a stress steroid in bony fishes) are discussed